Laticifer growth pattern is guided by cytoskeleton organization - Medina, Maria Camila; Sousa-Baena, Mariane S.; Van Sluys, Marie-Anne; Demarco, Diego (Frontiers in Plant Science, 2022)
Laticifers are secretory structures that produce latex, forming a specialized defense system against herbivory. Studies using anatomical approaches to investigate laticifer growth patterns have described their origin; however, their mode of growth, i.e., whether growth is intrusive or diffuse, remains unclear. Studies investigating how cytoskeleton filaments may influence laticifer shape establishment and growth patterns are lacking. In this study, we combined microtubule immunostaining and developmental anatomy to investigate the growth patterns in different types of laticifers. Standard anatomical methods were used to study laticifer development. Microtubules were labelled through immunolocalization of α-tubulin in three types of laticifers from three different plant species: nonanastomosing (Urvillea ulmacea), anastomosing unbranched with partial degradation of terminal cell walls (Ipomoea nil), and anastomosing branched laticifers with early and complete degradation of terminal cell walls (Asclepias curassavica). In both nonanastomosing and anastomosing laticifers, as well as in differentiating meristematic cells, parenchyma cells and idioblasts, microtubules were perpendicularly aligned to the cell growth axis. The analyses of laticifer microtubule orientation revealed an arrangement that corresponds to those cells that grow diffusely within the plant body. Nonanastomosing and anastomosing laticifers, branched or not, have a pattern which indicates diffuse growth. This innovative study on secretory structures represents a major advance in the knowledge of laticifers and their growth mode.